The behavior of small and large firms during business cycle episodes and during monetary policy episodes: A comparison of earlier and recent periods - Sung-Eun Yu (The University of Utah, Department of Economics, 2017)
I provide more evidence on the behavior of small and large firms, employing the Flow of Funds data, the QFR data and other sources. The empirical test to examine behavior of small and large firms is conducted in two ways: (1) by different episodes, tight monetary policy episodes and business cycles episodes and (2) by different time periods, Pre-1990 periods and Post-1990 periods. First, I find that a monetary shock and an NBER recession shock differently affect firms' short-term financing behavior. During recent periods, after a contractionary monetary shock, large firms increase their short-term debt more than small firms, whereas after an NBER recession shock, large firms decrease most balance sheet variables (including short-term debt) more than small firms. These findings suggest that small firms are more credit-constrained after a monetary policy shock, whereas large firms are more credit-constrained after an NBER recession shock. Second, I find that, after a contractionary monetary shock, during earlier periods, large firms decrease their short-term debt less than small firms, whereas during recent periods, large firms increase more than small firms. Although these findings appear to be contradictory, they are consistent in that small firms have continued to be more credit-constrained than large firms after contractionary monetary policy - at the time when demand for loans increases.
Keywords: E32; E51; E52; 330; monetary policy shock; business cycle shock; small firms; large firms